2022
DOI: 10.1097/mco.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal effects of diets low in fermentable oligosaccharides, disaccharides, monosaccharides and polyols

Abstract: Purpose of review Food ingestion is an exacerbator of gastrointestinal symptoms, regardless of origin. Sufferers mistakenly assume that they have suffered an allergic reaction to a given food. Although classical IgE-mediated allergic reactions are rarely culpable, evidence for a role for intolerance to certain carbohydrates in irritable bowel syndrome (IBS) and related conditions increases. This review assesses the status of a commonly implicated group of poorly absorbed carbohydrates (fermentable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(66 reference statements)
0
1
0
Order By: Relevance
“… 3 Moreover, the low FODMAP diet is very restrictive, needs the close follow-up of an experienced dietitian and the compliance is variable. 18 , 19 In addition, it has been shown that it could negatively affect the microbiome by reducing levels of Bifidobacteria spp. and short-chain fatty acids (SCFAs) production.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Moreover, the low FODMAP diet is very restrictive, needs the close follow-up of an experienced dietitian and the compliance is variable. 18 , 19 In addition, it has been shown that it could negatively affect the microbiome by reducing levels of Bifidobacteria spp. and short-chain fatty acids (SCFAs) production.…”
Section: Introductionmentioning
confidence: 99%